Progress in research on uric acid metabolism pathway - HU Xiao-hua; ZHANG Li-ming (Linchuang shenzangbing zazhi)
Uric acid is a product of sputum metabolism, and its crease is caused by increase in uric acid production and a decrease in uric acid excretion. The main metabolic pathway of uric acid is present in the kidney, and secondly in the intestine; and the excretion of uric acid is mainly dependent on the uric acid transporter. At present, a large number of studies have reported uric acid metabolic pathways are found in the kidney, and few reports show that the pathway exists in the intestines. Therefore, this paper reviews the domestic and international studies on the uric acid metabolism pathway from two aspects of kidney and intestine, and provides new ideas for reducing uric acid and treating uric acid-related diseases.